Ethnic aspects of hereditary breast cancer - P. A. Gervas; A. Yu. Molokov; E. V. Panpherova; L. Ph. Pisareva; N. V. Cherdyntseva (Сибирский онкологический журнал, 2019)
This study aimed to reveal the spectrum of BRca1 and BRca2 genes mutation in various ethnic groups of the Russian Federation. asystematic literature search includes data for the past 10 years and was conducted by using electronic databases of pubmed, eliBRaRY and ect.Material and methods. The review includes research data on the frequency of mutations of breast cancer-associated genes in various ethnic groups of the Russian Federation.Results. For «slavic» patients with a family history, the BRca1/2 mutation testing is the standard of care. in addition, the development of new antitumour drugs has resulted in improved survival rates. more than 1000 mutations of the BRca1 gene have been identified. Recent research is focused on the confirmation the beneficial effect of identified mutations. For the indigenous population (mongoloid ethnic groups), there are no standards for the treatment of inherited breast cancer. thus, the advances in molecular oncology for the treatment of hereditary breast cancer are not available for the indigenous population of the Russian Federation.Conclusion. In this context, the search for markers of early cancer detection and the development of criteria for therapy response are relevant for indigenous people. the development of new predictive and prognostic criteria of breast cancer among mongoloid ethnic groups with a family history will allow the innovative strategies for personalized molecular therapy to be developed.